Advancements in the use of manometry and impedance testing for esophageal functional disorders. (4th May 2019) - Savarino, Edoardo; Marabotto, Elisa; Bodini, Giorgia; Furnari, Manuele; Della Coletta, Marco; Ghisa, Matteo; Barberio, Brigida; Frazzoni, Marzio; De Bortoli, Nicola; Zentilin, Patrizia; Pellegatta, Gaia; Tolone, Salvatore; et al.
ABSTRACT: Introduction . The utilization of high-resolution manometry (HRM) has enhanced our understanding and assessment of esophageal motor disorders. Moreover, the combination of impedance technology with HRM (HRIM) has further improved our knowledge of esophageal physiology and the clinical evaluation of dysmotility, thanks to the addition of accurate measurement of bolus transit. Areas covered . This paper provides an overview of current knowledge in the use of HRIM for the study of esophageal functional disorders by reporting mainly the results of many publications and several systematic reviews in this field. Expert opinion . HRIM has represented a relevant improvement in the assessment of esophageal motility and has required the development of new metrics, such as the esophageal impedance integral ratio, the bolus flow time, the nadir impedance pressure and the impedance bolus height, which increase the evaluation of esophageal bolus transit. An extension of impedance is represented by functional lumen imaging probe (FLIP), which determines the biophysical properties and the distensibility of the esophagus and permits to detect contractility patterns not seen on HRM alone. We eagerly wait for a new and fruitful iteration of the Chicago Classification, now in version 3.0, which can cover the ongoing clinical experience of HRIM.